2023
DOI: 10.1021/acsinfecdis.3c00422
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Compositional Diversities of Campylobacter jejuni Outer Membrane Vesicles (OMVs) Drive Multiple Cellular Uptake Processes

Afruja Khan,
Avijit Sardar,
Pradip K. Tarafdar
et al.

Abstract: Naturally secreted outer membrane vesicles (OMVs) from gut microbes carry diverse cargo, including proteins, nucleic acids, toxins, and many unidentified secretory factors. Bacterial OMVs can shuttle molecules across different cell types as a generalized secretion system, facilitating bacterial pathogenicity and self-survival. Numerous mucosal pathogens, including Campylobacter jejuni (C. jejuni), share a mechanism of harmonized secretion of major virulence factors. Intriguingly, as a common gut pathogen, C. j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Cells were isolated after the suspension had been filtered through a cell strainer (40 μm) and centrifuged at 500 g for 10 min at RT. Isolated primary CEICs were maintained in RPMI 1640 (Gibco, Invitrogen) medium supplemented with 10% FBS, 100 IU/mL penicillin, and 100 μg/mL streptomycin at 37 °C with 5% CO 2 for 4–6 days until confluency reached to 70–80% …”
Section: Methodsmentioning
confidence: 99%
“…Cells were isolated after the suspension had been filtered through a cell strainer (40 μm) and centrifuged at 500 g for 10 min at RT. Isolated primary CEICs were maintained in RPMI 1640 (Gibco, Invitrogen) medium supplemented with 10% FBS, 100 IU/mL penicillin, and 100 μg/mL streptomycin at 37 °C with 5% CO 2 for 4–6 days until confluency reached to 70–80% …”
Section: Methodsmentioning
confidence: 99%
“…In brief, proteomic analyses of BEV content have confirmed that numerous virulence factors, representing all steps of C. jejuni pathogenesis, are packed into these vesicles [52], [62]. [69]. They reported that host cell-specific differences in BEV uptake from the extracellular milieu were mediated by heterogeneity in vesicles caused by underlying differences in the membrane phospholipids acquired from the source bacteria and the abundance of surface proteins.…”
Section: Implication Of Bevs In C Jejuni Virulencementioning
confidence: 99%